2018
DOI: 10.1007/s10461-018-2206-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religious Service Attendance, Psychosocial and Behavioral Determinants of Antiretroviral Therapy (ART) Adherence: Results from HPTN 063 Cohort Study

Abstract: Early and sustained antiretroviral therapy (ART) adherence can suppress the HIV virus in individuals and reduce onward transmission of HIV in the population. Religiosity has been associated with better HIV clinical outcomes. Data are from a longitudinal, observational study of 749 HIV-infected individuals from Brazil, Zambia, and Thailand (HPTN 063). Ordered logistic regression assessed whether religious service attendance was associated with ART adherence (self-reported and plasma HIV-RNA) and moderated the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
(78 reference statements)
0
3
1
1
Order By: Relevance
“…The inclusion of religion and spirituality in quantitative research related to HIV among MSM is limited, 39 and prior research has shown that religious involvement may be positively associated with antiretroviral therapy adherence. 40 In our study, weekly religious service attendance was not associated with willingness to start PrEP. Discussion of condom use with male partners was another variable that was not significantly associated with willingness to start PrEP.…”
Section: Family and Community Healthcontrasting
confidence: 53%
“…The inclusion of religion and spirituality in quantitative research related to HIV among MSM is limited, 39 and prior research has shown that religious involvement may be positively associated with antiretroviral therapy adherence. 40 In our study, weekly religious service attendance was not associated with willingness to start PrEP. Discussion of condom use with male partners was another variable that was not significantly associated with willingness to start PrEP.…”
Section: Family and Community Healthcontrasting
confidence: 53%
“…The sixth mechanism is circumcision. The seventh mechanism is alcohol use, which we identified as a unique category given its relationship to both religion and HIV [47,48].…”
Section: Plos Onementioning
confidence: 99%
“…Verificou-se que a maioria das pesquisas foi desenvolvida no continente africano (n = 23) e norte americano (n = 13). Destaca-se que apenas um trabalho foi realizado em mais de um país, que avaliou a associação entre o atendimento religioso e adesão à TARV no Brasil, em Zâmbia e na Tailândia (Ransome et al, 2019).…”
Section: Perfil Dos Estudos Recuperadosunclassified